2020
DOI: 10.1111/jomf.12669
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Orientation, Geographic Proximity, and Contact Frequency Between Adult Siblings

Abstract: The aim of this study is to provide the first systematic analysis of differences in the closeness of sibling relations between lesbian, gay, and bisexual (LGB) and heterosexual adults. Background: Across countries, LGB people experience poorer socioeconomic and health outcomes than heterosexual people. Although the reasons for this disadvantage are complex, low levels of family support have been recurrently identified as an important contributor. However, the available literature has concentrated on relations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Social support can buffer against and help an individual cope with the negative effects of stigmatization, which is common among sexual minority groups like GBM, who are more likely to experience social rejection in their family and peer networks (Hatzenbuehler, 2009; Meyer, 2003; Perales & Plage, 2020). Thus, social supports may be particularly important for GBM; indeed, members of sexual minority groups tend to experience a stronger positive effect of social support compared with heterosexual people (Hsieh, 2014).…”
Section: Social Support Among Gbmmentioning
confidence: 99%
“…Social support can buffer against and help an individual cope with the negative effects of stigmatization, which is common among sexual minority groups like GBM, who are more likely to experience social rejection in their family and peer networks (Hatzenbuehler, 2009; Meyer, 2003; Perales & Plage, 2020). Thus, social supports may be particularly important for GBM; indeed, members of sexual minority groups tend to experience a stronger positive effect of social support compared with heterosexual people (Hsieh, 2014).…”
Section: Social Support Among Gbmmentioning
confidence: 99%
“…In addition, a growing body of literature has started to consider the roles of sexual and gender minority identities in marital and parent–adult child ties (Connidis & Barnett, 2019; Reczek, 2020). A recent study showed that individuals who identified as lesbian, gay, or bisexual had less contact with their siblings than did individuals who identified as heterosexual (Perales & Plage, 2020). Future scholarship should continue to consider how sexual and gender minority identities have an impact on sibling relationships.…”
Section: Future Directionsmentioning
confidence: 99%
“…For example, existing literature suggested that siblings are more likely to be related in criminal behavior, specifically those who are closely spaced (van de Rakt et al, 2009). In addition, siblings tend to be more distant when they differ in terms of sexual orientation (i.e., hetero-and homosexuality) or in the case of siblings with mental disabilities (Kaminsky & Dewey, 2001;Perales & Plage, 2020). Future studies could investigate these topics from different angles or uncover sibling (dis)similarities in other domains.…”
Section: Discussionmentioning
confidence: 99%